IMPLEMENTATION OF CHILD-FRIENDLY PESANTREN IN AN EFFORT TO PREVENT VIOLENCE AGAINST STUDENTS IN ISLAMIC BOARDING SCHOOLS - RAHMANUDIN, II; YAKIN, PAJRI AINUL; UMAM, MUHAMMAD KHOERUL (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
The rise of violence against children in the pesantren environment has been circulating in the mass media. So the problems that occur invite educators to be able to implement child-friendly pesantren to prevent violence against students in Islamic boarding schools. So the purpose of this study is to find out how the implementation of child-friendly pesantren in the pesantren environment, especially the Muthmainnatul Qulub AL Islami Pesantren Cibinong Bogor. And to what extent this boarding school has implemented Child-Friendly Pesantren by the guidelines of the Ministry of Religion? The research method used is a descriptive qualitative method with a case study approach. The data is taken from interview data, documentation, and observation. The data analysis uses triangulation data analysis. The result is that Pondok Pesantren Muthmainnatul Qulub AL Islami Cibinong Bogor West Java has carried out child-friendly pesantren procedures quite well with a percentage of 50% implementation but there are still many shortcomings and the need for a very deep evaluation to support the child-friendly pesantren program. So that there are no more cases of violence even if only in the form of bullying. ABSTRAKMaraknya kekerasan pada anak di lingkungan pesantren sudah beredar di media masa. Sehingga problematika yang terjadi mengundang pada pendidik untuk bisa mengimplementasikan pesantren ramah anak dalam upaya mencegah kekerasan pada santri di Pondok Pesantren. Maka tujuan penelitian ini adalah mengetahui bagaimana implementasi pesantren ramah anak di lingkungan pesantren khususnya Pesantren Muthmainnatul Qulub AL Islami Cibinong Bogor. Dan sejauhmana pondok pesantren ini sudah mengimplementasikan Pesantren Ramah Anak sesuai dengan pedoman dari Kemenag. Metode penelitian yang digunakan ialah metode kualitatif deskriptif dengan pendekatan studi kasus. Adapun data diambil dari data wawancara, dokumentasi dan observasi. Analisis datanya menggunakan analisis data tringulasi. Hasilnya adalah bahwa di Pondok Pesantren Muthmainnatul Qulub AL Islami Cibinong Bogor Jawa Barat, sudah melakukan prosedur pesantren ramah anak dengan cukup baik dengan persentasi penerapan 50% namun masih banyak kekurangan dan perlunya evaluasi yang sangat dalam mendukung program pesantren ramah anak. Sehingga tidak ada lagi kasus kekerasan walaupun hanya dalam bentuk bullying.